Aggressive and cannibalistic behavior of African catfish larvae: effect of different doses of methyltestosteron injecting to female broodstock and larval stocking densities - Rahmadiah, Triayu; Junior, Muhammad Zairin; Alimuddin, Alimuddin; Diatin, Iis (Indonesian Society of Scientific Aquaculture (ISSA), 2019)
ABSTRACT This study aimed to evaluate the effect of 17α-methyltestosterone hormone (MT) injecting to female broodstocks and stocking densities on the aggressive and cannibalistic behavior of African catfish larvae. Two-day-old post-hatching larvae were used in this experiment. Larval rearing was started at three-day-old post-hatching (body weight 0.004 ± 0.003 g and total length 0.2 ± 0.05 cm) in a 40 cm×30 cm× 25 cm rearing aquaria. This study used a completed randomized factorial design which consisted of two factors. The first factor were the larvae from females broodstocks without MT injection (0 μg/g body weight) (A), injected with MT (1 μg/g body weight) (B), and injected with MT (2 μg/g body weight) (C), while the second factor were larval stocking densities of 3.000/m2 (V1) and 6.000/m2 (V2), with three replications. The results showed that the larvae from female broodstocks injected with MT 2 μg/g body weight (C) and stocking densities 6.000/m2 (V2) increased the aggressiveness of swim and decreased cannibalism. The highest cannibalistic behavior occurred from 00.00‒06.00.Keyword: aggressiveness, cannibalism, Clarias gariepinus, methyltestosterone ABSTRAKPenelitian ini bertujuan untuk mengevaluasi pengaruh hormon 17α-metiltestosteron (MT) yang diinjeksikan pada induk betina dan padat tebar terhadap tingkat agresivitas dan kanibalisme larva ikan lele. Ikan uji yang digunakan adalah larva berumur dua hari setelah penetasan. Pemeliharaan larva dimulai saat larva berumur tiga hari setelah penetasan (bobot tubuh 0,004 ± 0,003 g dan panjang total 0.2 ± 0.05 cm) yang dipelihara di dalam akuarium berukuran 40 cm×30 cm×25 cm. Penelitian ini menggunakan rancangan acak lengkap faktorial yang terdiri atas dua faktor. Faktor yang pertama adalah larva dari induk tanpa diinjeksi dengan hormon MT (0 μg/g bobot tubuh) (A), diinjeksi dengan hormon MT (1 μg/g bobot tubuh) (B), dan diinjeksi dengan hormon MT (2 μg/g bobot tubuh) (C), sedangkan faktor yang kedua adalah padat tebar 3.000 ekor/m² (V1) dan 6.000 ekor/m² (V2), dengan tiga kali ulangan. Hasil penelitian menunjukkan bahwa larva ikan lele dari induk yang diinjeksi hormon MT dosis 2 µg/g bobot tubuh dan dipelihara pada padat tebar tinggi 6.000 ekor/m² (V2) dapat meningkatkan agresivitas berenang dan menurunkan kanibalisme. Tingkat kanibalisme tertinggi terjadi pada pukul 24.00‒06.00 WIB. Kata kunci: agresivitas, kanibalisme, Clarias gariepinus, metiltestosteron